Pemanfaatan Lingkungan Alam Sebagai Sumber Pembelajaran - Nur Indah Sari; Herlina; Karmila; Sulkifli (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The environment in the area can be used as a tourist object as a source of learning. One of the impacts of the existence of tourist objects is in the form of knowledge exchange. By utilizing the environment in the form of tourist objects as a source of learning can cause students to help preserve nature and culture, increase students' love and care for the environment, students are able to open new insights about the outside world, and students can experience learning that is interesting, creative and not boring. There are lots of tourist objects that can be used as a place to learn directly in their environment by observing, finding out, describing, and comparing various things in the surrounding environment. This can develop the skills and abilities of SMK NEGERI 9 PANGKEP students. The natural environment in the Pangkep area has beautiful mountains, charming hills, and there are also waterfalls that store cool springs. In the Pangkep Region there are so many unique and distinctive tourist objects that are so interesting to be used as learning resources. Tourism students' English learning activities are directed to visit tourist objects in their area, so that students can get to know tourist objects in their area better and can introduce their tourist objects not only to the local community, but with the ability to learn English in introducing tourist objects in their area. , it is hoped that students can introduce tourist objects in their area to the outside community.